Analysis of Emotional Intelligence of Class V Students Through the RADEC Learning Model - Mia Komariah; Nurnaningsih; Wahyu Sopandi; Atep Sujana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Social conflicts such as bullying, anti-patience, and individualistic attitudes among elementary school students are caused by students' lack of emotional intelligence. This study aimed to analyze the emotional intelligence of grade 5 elementary school students through the RADEC learning model. This study uses a qualitative approach with a descriptive analysis method. The instruments used were student activity observation sheets, student interviews, and documentation of learning activities using the RADEC model. The data analysis is data reduction, presentation, describing, and verifying conclusions. The participants in this study were 29 grade 5 students at one of the public elementary schools in the city of Bandung. Based on the research, it can be concluded that emotional intelligence can be grown through the RADEC learning model. Refers to the five elements of emotional intelligence possessed by students, namely self-awareness, which is shown by recognizing the emotions being felt. Managing emotions is demonstrated by knowing the response that must be given to an event, utilizing emotions productively, which is characterized by understanding the attitude that must be done towards a phenomenon, empathy, which is shown by caring for others, and fostering relationships which are demonstrated by liking interactions with other people.